Averaging of set-valued impulsive systems - Perestyuk, N. A.; Skripnik, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We give a review of the development of ideas of the averaging method for some classes of set-valued impulsive systems(impulsive differential inclusions, impulsive differential equations and inclusions with Hukuhara derivative, and impulsivefuzzy differential equations and inclusions).